2022
DOI: 10.1021/acs.cgd.2c00762
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework Seeding to Drive Phase Selection and Overcome Synthesis Limitations

Abstract: Seeding during the synthesis of metal−organic frameworks (MOFs) enhances control over phase expression in synthesis conditions with high concentrations of metal and linker enabling reduced solvent quantities. Dramatic improvements to yield over unseeded conditions are achieved. Phase direction via the seeding method was explored for four different MOFs: Mg-MOF-74, DMOF-1, SNU-70, and UiO-66. The MOFs employed vary in terms of metal identity, secondary building unit, and linker, which demonstrates broad applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 22 publications
2
24
1
Order By: Relevance
“…In particular, the need for liters of solvent(s) and disproportionate quantities of acid modulators often limit MOF synthesis to sub-gram quantities. Recently, Matzger and coworkers, 137 along with our group, 138 have found that much higher reaction concentrations (up 1 M in some cases) can be used to produce high-quality MOFs with significantly reduced solvent waste. In a similar vein, we carried out a structure-property study to identify the optimal modulator for Zr-MOF synthesis, with the goal of reducing the amount of modulator required to produce highly crystalline material.…”
Section: Robustness Of Mofs For Organic Synthesismentioning
confidence: 99%
“…In particular, the need for liters of solvent(s) and disproportionate quantities of acid modulators often limit MOF synthesis to sub-gram quantities. Recently, Matzger and coworkers, 137 along with our group, 138 have found that much higher reaction concentrations (up 1 M in some cases) can be used to produce high-quality MOFs with significantly reduced solvent waste. In a similar vein, we carried out a structure-property study to identify the optimal modulator for Zr-MOF synthesis, with the goal of reducing the amount of modulator required to produce highly crystalline material.…”
Section: Robustness Of Mofs For Organic Synthesismentioning
confidence: 99%
“…8 Unfortunately, the large solvent volumes required for traditional solvothermal synthesis necessitate the use of liters of solvent to produce sub-gram quantities of MOF, contributing greatly to the cost of MOFs on scale and generating significant waste. 11 Solvothermal MOF syntheses at higher concentrations are rare, [12][13][14][15][16] as poorly crystalline or low surface area materials are typically isolated instead due to the rapid precipitation of products from solution. 13,[17][18][19][20][21] The MOF-74, CPO-27, or M2(dobdc) (M = Mg, Mn, Fe, Co, Ni, Cu, Zn, Cd; dobdc 4− = 2,5-dioxido-1,4-benzenedicarboxylate) family of frameworks embodies the aforementioned synthetic challenges (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…A more user-friendly approach would be to simply conduct solvothermal synthesis at much higher reaction concentrations (e.g., 1.00 M, an approximately 100-fold increase). 10,11 However, examples of successful MOF syntheses even at intermediate concentrations (0.15-0.25 M) remain surprisingly scarce; 10,[12][13][14] more common instead are reports of poorly crystalline products, unusual morphologies, low surface area materials, or different phases forming at high concentrations due to the rapid precipitation of products from solution. 10,11,[15][16][17][18] These findings beg the question: can MOFs effectively self-assemble at high reaction concentrations?…”
Section: Introductionmentioning
confidence: 99%
“…10,11 However, examples of successful MOF syntheses even at intermediate concentrations (0.15-0.25 M) remain surprisingly scarce; 10,[12][13][14] more common instead are reports of poorly crystalline products, unusual morphologies, low surface area materials, or different phases forming at high concentrations due to the rapid precipitation of products from solution. 10,11,[15][16][17][18] These findings beg the question: can MOFs effectively self-assemble at high reaction concentrations? MOFs constructed from Zr6 nodes (Zr-MOFs), [19][20][21] as well as isostructural Hf-based MOFs (Hf-MOFs), 22 exemplify the challenges and opportunities associated with high-concen-tration MOF synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation